Classification of the Tasks of Local Governmental Units in Poland in the Light of Fundamental Legal Acts — Discussion of Selected Aspects - Marta Mulawa (Barometr Regionalny)
The purpose of this article is the presentation of a summary of tasks which local governments in Poland perform and to illustrate their diversity and specificity. The article deals with local government and its specific tasks, which every level of self-government carries out. It is true that self–government is a very important institution operating in most democratic countries in the world. The proper structure of local governmental bodies, as well as the rules of their work and how they make decisions, support the performance of tasks by individual units. The issue of local government concerns its tasks. It is very extensive. These elements are regulated by the Constitution of the Republic of Poland and laws, especially the Act on Commune Self-Government, the Act on County Government and the Act on Voivodship Government. Self-government is the most democratic form of government as an instrument of socialization in the exercise of public authority. Emphasing that local government is a fundamental cell in public administration is one of the aims of this article. Local government carries out tasks in appropriate forms, supported by the European Charter of Local Self Government and national legislation. Being fundamental, universal and compulsory, local government creates a community. Otherwise of an administrative nature, local government is a political phenomenon. The essential feature of the structure of local government in Poland is the fact that local government performs a substantial part of public administration at the level of commune as well as those of district and voivodship. Tasks of local government in Poland are dualistic. Local authorities have powers of their own while performing the tasks assigned to them by law and government. Moreover an important part of this article is about local government as a form of decentralization of public authority.